Analysis on Cable Fault Tolerance Kinematics Space of Cable-driven Snake-arm Robots - Chen Huiqing; Yang Taiwei (Jixie chuandong)
Snake-arm robots attract extensive attention and research because of its compact structure, flexible motion and operational ability in narrow space and dangerous working conditions. In this study, coordinates are built according to Denavit-Hartenberg (D-H) method based on structure characteristics of cable-driven snake-arm robots , and then kinematics analysis is conducted with Monte Carlo method. The reachable space ranges of the cable-driven snake-arm under different modes is simulated by Matlab. The reachable space ranges have been determined for the intact condition of the cable-driven snake-arm when failure and fracture of any single driving cable are presented in the snake-arm. The results not only reveal the influence of different arm segments on the reachable space of snake-arm robots, but also lay a foundation for the arm segments structure design optimization and the intelligent trajectory planning of the cable-driven snake-arm.